2016
DOI: 10.1016/j.ijnurstu.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in research on language barriers in health care since 2003: A cross-sectional review study

Abstract: Background Understanding how to mitigate language barriers is becoming increasingly important for health care providers around the world. Language barriers adversely affect patients in their access to health services; comprehension and adherence; quality of care; and patient and provider satisfaction. In 2003, the United States (US) government made a major change in national policy guidance that significantly affected limited English proficient patients’ ability to access language services. Objective The obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 18 publications
1
55
0
2
Order By: Relevance
“…21 Studies have documented the negative impact of language barriers on not only access to care but quality of care. 22 Access to rehabilitation for children with TBI is important because an association between access and better outcomes has been noted in adult patients 23 and rehabilitation services are recommended for patients to achieve maximum improvements in physical, cognitive and behavioral functioning after TBI. 1 …”
Section: Discussionmentioning
confidence: 99%
“…21 Studies have documented the negative impact of language barriers on not only access to care but quality of care. 22 Access to rehabilitation for children with TBI is important because an association between access and better outcomes has been noted in adult patients 23 and rehabilitation services are recommended for patients to achieve maximum improvements in physical, cognitive and behavioral functioning after TBI. 1 …”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers have reported that language barriers contribute to health disparities by posing a significant threat not only to access to medical treatments, but also to the quality of care, provider-patient relationship, treatment adherence, patient satisfaction, and health outcomes [1][2][3][4][5][6][7][8]. Despite such well documented correlations between language barriers and health disparities, it is rarely examined how exactly language barriers contribute to health disparities [2]. To create better interventions or countermeasures to mitigate the health disparities that individuals with language barriers experience, it is necessary to know the ways that language barriers contribute to health disparities [9].…”
Section: Introductionmentioning
confidence: 99%
“…Jezikovne prepreke lahko definiramo kot pomanjkanje komunikacije med dvema osebama, ki govorita tuj jezik ali drugo narečje (Collins English Dictionary, 2017). Jezikovne prepreke vplivajo na kakovost zdravstvene nege v zdravstvenem sistemu, saj onemogočajo dobro in učinkovito komunikacijo med medicinsko sestro in pacientom (Schwei, et al, 2016). Tako prihaja do manj uspešne izmenjave informacij, kar lahko vodi do napak v zdravstvu (Bofulin, et al, 2016).…”
Section: Uvodunclassified